2013
DOI: 10.1074/jbc.m112.444414
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Mirror-image DNA/RNA Aptamer Inhibits Glucagon and Acutely Improves Glucose Tolerance in Models of Type 1 and Type 2 Diabetes

Abstract: Background: An increased glucagon/insulin ratio is known to contribute to hyperglycemia in diabetes.Results: NOX-G15, a mirror-image mixed DNA/RNA glucagon-neutralizing aptamer, was identified. It improved glucose tolerance in models of type 1 and 2 diabetes.Conclusion: NOX-G15 may be useful for treatment of type 1 and 2 diabetes.Significance: The new therapeutic candidate may help to reduce insulin need in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Similarly, glucagon receptor antibodies have been shown to lower hyperglycemia in T2D (15), but this is the first demonstration, to our knowledge, of normalization of glycemia and HbA1c in complete insulin deficiency, a result that, to our knowledge, has never been achieved with existing therapies. Previous neutralization of glucagon itself reduced, but did not normalize, blood glucose levels (27)(28)(29). Synthetic glucagon receptor antagonists (30-33) similarly improved the diabetes but did not normalize it.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, glucagon receptor antibodies have been shown to lower hyperglycemia in T2D (15), but this is the first demonstration, to our knowledge, of normalization of glycemia and HbA1c in complete insulin deficiency, a result that, to our knowledge, has never been achieved with existing therapies. Previous neutralization of glucagon itself reduced, but did not normalize, blood glucose levels (27)(28)(29). Synthetic glucagon receptor antagonists (30-33) similarly improved the diabetes but did not normalize it.…”
Section: Discussionmentioning
confidence: 89%
“…In the case of antibody drug conjugates, which utilize this linkage, the long systemic circulation half-lives of these molecules, *10-20 days [27,28], has led investigators to utilize hindered disulfides that bear a methyl group adjacent to one or both sides of the disulfide linkage to further increase serum stability [26,27]. However, aptamers display clearance rates in minutes [29] which can be extended by conjugation to high molecular weight (20-40 kDa) PEG, which have reported half-lives ranging from 3 to 12 h [29][30][31]. rGel has a molecular weight of 28 kDa, thus we would expect our aptamerrGel conjugates to behave similarly.…”
Section: Discussionmentioning
confidence: 99%
“…The isolated aptamer sequences can be chemically synthesised as L-RNA stereoisomers (''Spigelmers''), that are resistant to nuclease cleavage and bind specifically to the natural target (composed of L-amino acids) [9]. Vater et al and Purschke et al have demonstrated that mixed L-DNA/L-RNA Spiegelmers have sufficient stability to mediate clinically-relevant biological effects in vivo, the specific inhibition of glucagon in mouse models of type 1 and type 2 diabetes [10], and neutralisation of sphingosine-1-phosphate, a mediator of angiogenesis [11]. In future it may be possible to evolve Spiegelmers directly using polymerases synthesised from D-amino acids.…”
Section: Stabilitymentioning
confidence: 98%